Association Between Intraoperative Low Blood Pressure and Development of Surgical Site Infection After Colorectal Surgery: A Retrospective Cohort Study. Issue 6 (December 2016) - Babazade, Rovnat; Yilmaz, Huseyin O.; Zimmerman, Nicole M.; Stocchi, Luca; Gorgun, Emre; Kessler, Hermann; Sessler, Daniel I.; Kurz, Andrea; Turan, Alparslan
Abstract : Objective: We tested the primary hypothesis that surgical site infections (SSIs) are more common in patients who had longer periods of intraoperative low blood pressure. Our secondary hypothesis was that hospitalization is prolonged in patients experiencing longer periods of critically low systolic blood pressure (SBP) and/or mean arterial pressure (MAP). Background: Hypotension compromises local tissue perfusion, thereby reducing tissue oxygenation. Hypotension might thus be expected to promote infection, but the extent to which low blood pressure contributes remains unclear. Methods: We considered patients who had colorectal surgery lasting at least 1 hour at the Cleveland Clinic between 2009 and 2013. The duration of hypotensive exposure and development of SSI was assessed with logistic regression; the association between hypotensive exposure and duration of hospitalization was assessed with Cox proportional hazard regression. Results: A total of 2521 patients were eligible for analysis. There was no adjusted association between SBP hypotension < 80 mm Hg and SSI, with an estimated odds ratio (95% confidence interval) of 0.97 (0.81, 1.17) per 5-minute increase in SBP hypotension ( P = 0.54). There was also no adjusted association between MAP hypotension time and SSI, with estimated odds ratio of 0.97 (0.81, 1.17) for a 5-minute increase in MAP hypotension < 55 mm Hg time ( P = 0.71). There was no association between duration of hypotension and time to discharge. Conclusions: Intraoperative hypotension does not seem to be a clinically important predictor of SSI after colorectal surgery, probably because the outcomes are overwhelmingly determined by other baseline and surgical factors—and perhaps postoperative hypotension. Abstract : Supplemental Digital Content is available in the text